Factors instigating employee turnover intention amid COVID-19 - Dayal, Gopali; Verma, Pooja (International journal of health sciences, 2022)
The present study intends to analyze the factors affecting employee turnover intention. For this, an exhaustive literature review was done. Fifteen elements were shortlisted that directly affect turnover intention, i.e., Leadership styles, Demographic variables, Salary, Organizational culture, Job stress, Organizational commitment, Organizational Justice, Organizational climate, Promotion opportunities, Job Satisfaction, and Work pressure. Further, the study aims to gauge how these factors contributed to turnover intentions amid pandemics.